Pattern and predictors of energy drink consumption in medical students and physicians (2019)
Background: The consumption of energy drinks is increasing among students of medicine and recent medical graduates. A cross-sectional study that uses a questionnaire designed to gather information on energy drinks consumption analyzes this problem. Methods: This cross-sectional study used a questionnaire designed to gather information on energy drinks consumption of medical students and physicians. Four hundred fifty questionnaires were completed. Results: The majority of the questionnaires was completed in Colombia; the rest were completed in North American (n: 8, 1.8%), Central America (n: 17, 3.8%), South America (n: 86, 19.1%), and Europe (n: 2, 0.4%). There is a high frequency of energy drinks consumption among medical students and physicians; for every five physicians or medical students who consume energy drinks, one is not a consumer. Conclusions: There is a great need to build awareness among physicians and medical students concerning these drinks. This study identifies a risk behavior, and it summons the international medical community, health institutions, universities, and trade associations to conduct health promotion and prevention activities, including the practice of healthy habits in medical students and physicians to deal with this problem. © 2019, © 2019 Taylor and Francis Group, LLC.